Visualizing the Shift: Word Cloud Analysis of Pradhan Mantri Jan Aushadhi Suvidha Sanitary Napkin - Srivastava, Diksha; Prasad Lal, Sudhanand; Shukla, Gyan (Indian Journal of Extension Education, 2024)
Word cloud is a graphical representation of knowledge that lets a viewer acquire a quick and intuitive impression of a text. The study was conducted in Muzaffarpur and Samastipur districts of Bihar to find out the frame of mind of 160 respondents regarding menstruation and menstrual-related products before and after the commencement of Jan Aushadhi Suvidha Sanitary Napkin (launched by the Government of India in 2018) through word cloud. Analysis was done for both positive and negative frame of mind. High Price, embarrassment, uncomfortable, social restriction, isolation, dependence, stigma, taboo, pain, and itching, were negative aspects. Affordable price, easily available, awareness, hygiene, social participation, empowerment, independence, openness, menstrual health, and rash-free were positive aspects. Utilizing word clouds to analyze women’s expressions regarding menstruation provided valuable insights into their frame of mind. It reveals recurring themes, concerns, and emotions, assisting in effectively identifying and addressing menstrual-related difficulties. The data-driven strategy (through word cloud) is critical for improving menstrual health and well-being.
Keywords: Biodegradable; Frame of mind; Jan Aushadhi Suvidha Sanitary Napkin (JASSN); Menstruation; Sanitary Napkin; Tag Cloud; Word Cloud